A Policy Framework for Regulating the Use of Cryptocurrency as a Means of Payment in Thailand - Suwannawong Sauer, Wasinee (Rajapark Journal, 2026)
This research aims to 1) examine and analyze the legal framework governing the use of cryptocurrency as a means of payment in Thailand, 2) analyze the structural fragmentation of financial regulatory governance, and 3) propose a hierarchical co-regulatory framework to enhance normative coherence and regulatory legitimacy. The expansion of the digital asset market challenges traditional legal concepts of money, payment instruments, and state monetary sovereignty. Under the Emergency Decree on Digital Asset Businesses B.E. 2561, cryptocurrency is classified as a digital asset and regulated within the capital market framework. However, its function as a means of payment is also subject to payment systems law and central banking law, which together shape the country’s financial regulatory structure and give rise to conceptual ambiguity and overlapping regulatory authority. This study adopts a qualitative research approach by analyzing legal provisions, regulatory notifications, and relevant policy documents, and by conducting comparative legal analysis to assess integrated regulatory models. The research findings were as follows: 1) Thai law does not explicitly prohibit the use of cryptocurrency as a means of payment, but regulatory constraints create legal uncertainty. 2) the existing legal framework leads to fragmented and overlapping regulatory authority, and 3) a hierarchical co-regulatory framework should be developed to enhance legal certainty while maintaining financial stability and promoting innovation.